1994
DOI: 10.1002/hep.1840190214
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of alcohol and aldehyde dehydrogenase genes and alcoholic cirrhosis in chinese patients

Abstract: Liver alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH), the principal enzymes responsible for the oxidation of ethanol, are polymorphic at the ADH2, ADH3 and ALDH2 loci in human beings. Our previous studies have shown that, compared with nonalcoholic individuals, Chinese alcoholic patients without liver disease had significantly lower frequencies of the ADH2*2 and ADH3*1 alleles, which encode high maximum velocity beta 2- and gamma 1-ADH subunits, respectively, as well as a lower frequency of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 31 publications
4
84
0
1
Order By: Relevance
“…However, the precise mechanism(s) of action behind this mitochondrial enzyme-induced reversal against alcohol-induced hepatic injury remains elusive. Epidemiological evidence has suggested a tie between polymorphisms of genes involved in the metabolism of alcohol including ALDH2 and alcoholic liver diseases [32-35]. Liver injury may be caused by direct toxicity of alcohol or its metabolic byproducts, as well as by inflammation induced by these byproducts[27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanism(s) of action behind this mitochondrial enzyme-induced reversal against alcohol-induced hepatic injury remains elusive. Epidemiological evidence has suggested a tie between polymorphisms of genes involved in the metabolism of alcohol including ALDH2 and alcoholic liver diseases [32-35]. Liver injury may be caused by direct toxicity of alcohol or its metabolic byproducts, as well as by inflammation induced by these byproducts[27].…”
Section: Discussionmentioning
confidence: 99%
“…[29] reported that the homozygous ALDH2*2/*2 genotype is present at a very low frequency (0-0.3 per cent) in alcoholic patients, compared with 3-12 per cent among non-alcoholic subjects. The heterozygous ALDH2*1/*2 genotype has been found to be present in 6-17 per cent of alcohol-dependent subjects, compared with 30-45 per cent of non-alcoholic subjects [5,33,34]. This difference in ALDH2*2 allele frequency between alcoholic and non-alcoholic subjects has been postulated to be responsible for the phenomenon of adverse responses to alcohol consumption, such as facial flushing, nausea and tachycardia in individuals with the inactive form of the enzyme [29].…”
Section: Discussionmentioning
confidence: 99%
“…Tolerance (or intolerance) for alcohol, for example, appears heritable (cf. Chao et al 1994;Newmark et al 1998;Schuckit 1994;Schuckit and Smith 1996). However, the risk factors for diabetes and hypertension (e.g., obesity, stress, and inactivity) are also all strongly linked to family traditions, culture, and personal preferences (cf.…”
Section: Addiction As Voluntary Behaviormentioning
confidence: 99%